PARTISIPASI GENDER DALAM PENGELOLAAN SAMPAH RUMAH TANGGA DI KECAMATAN LUBUK KILANGAN KOTA PADANG - Samsir, Rosita Raudho; Ernawati, Ernawati (JURNAL BUANA, 2024)
This study aims to describe (1) gender participation in household waste management in Lubuk Kilangan District, Padang City. (2) the extent of gender participation behavior in household waste management in Lubuk Kilangan District, Padang City. This research uses descriptive qualitative method. As for the informant data, namely women in the household, men in the household, as well as people involved in waste management outside the household totaling 30 people. Data collection techniques used are observation, interviews, and documentation. The data validity test was carried out through triangulation techniques, then analyzed by data reduction, data presentation and conclusions for writing. The results of the study show that (1) the form of participation in waste management is by giving financial (financial) contributions that are paid monthly, as well as making donations such as sweeping houses and yards which are dominated by women, disposing of garbage which are dominated by men and mutual cooperation. Those who participate more in household waste management are the housewives themselves. (2) The behavior of gender participation in waste management uses the 3R principles of waste destruction, namely open dumping and individual incineration.